A Systematic Review on Indoor Environmental Quality in Naturally Ventilated School Classrooms: A Way Forward - Nishant Raj Kapoor; Ashok Kumar; Chandan Swaroop Meena; Anuj Kumar; Tabish Alam; Nagesh Babu Balam; Aritra Ghosh (Advances in Civil Engineering)
This review presents the existing state-of-the-art practices of indoor environmental quality (IEQ) in naturally ventilated school buildings and is mainly focused on the components of IEQ like thermal comfort, indoor air quality with ventilation, and visual and acoustic comfort. This article also discusses the impacts of COVID-19 on naturally ventilated school buildings, highlighting the obviousness of dynamic applications that concentrate on reducing COVID-19 effects in naturally ventilated school buildings. The importance of the concerned issues and factors are discussed in detail for future research direction. This review is a step toward the development of the IEQ standard for naturally ventilated school buildings.